A Study on the Psychological Analysis System Using Machine Learning - Young Lee, Ki; Ho Kim, Kyu; Jin Kang, Jeong; Jai Choi, Sung; Soon Im, Yong; Seok Choi, Gyoo (International Journal of Engineering and Technology, 2018)
Real-time facial expression recognition and analysis technology is recently drawing attention in areas of computer vision, computer graphics, and HCI. Recognition of userâ€™s emotion on the basis of video and voice is drawing particular interest. The technology may help managers of households or hospitals. In the present study, video and voice were converted into digital data through MATLAB by using PCA(Principal Component Analysis), LDA(Linear Discriminant Analysis), KNN(K Nearest Neighbor) algorithms to analyze emotions through machine learning. The manager of the psychological analysis counseling system may understand a userâ€™s emotion in an smart phone environment. This system of the present study may help the manager to have a smooth conversation or develop a smooth relationship with a user on the basis of the provided psychological analysis results.Â